EVALUASI PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN RAWAT JALAN DI RUMAH SAKIT EFARINA ETAHAM KOTA PEMATANGSIANTAR PERIODE APRIL - JUNI TAHUN 2024 - Wilson Samosir; Meyana Marbun, Hekdin Marsius Sipayung, Jesita Pratiwi Siagian (Jurnal Kesehatan, 2025)
Hypertension is an increase in systolic blood pressure of more than equal to 140 mmHg and diastolic blood pressure of more than equal to 90 mmHg (Ministry of Health, 2021). Data from the World Health Organization (WHO) states that hypertension is one of the causes of premature death throughout the world. By 2020 around 1.56 billion adults will be living with hypertension. The World Health Organization (WHO) notes that currently the global prevalence of hypertension is 22% of the world's total population. This study aims to broadcast the use of hypertension medication in patients at the Efarina Etaham Hospital, Pematangsiantar City for the period April- June 2024. Based on five indicators, namely the right indication, the right patient, the right drug, the right dose, the right duration of drug administration. create systematic, factual and accurate descriptions of images, or paintings regarding the facts, characteristics and relationships between the phenomena being marketed (Savira &Suharsono, 2019). This research was conducted on 80 medical records with a diagnosis of hypertension with or without comorbidities who received antihypertensive medication for the period April-June 2024. The results of the study showed that the appropriate evaluation of the use of antihypertensive medication was obtained, namely 100% correct indication, 100% correct patient, 100% correct medication. of 100% and the correct dose is 100%.